Peningkatan Profitabilitas Melalui Efisiensi Modal Kerja dan Likuiditas Pada Perusahaan Terdaftar di Jakarta Islamic Index (JII) - Monalisa, Helen; Asnaini, Asnaini (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to analyze the increase in profitability through working capital efficiency and liquidity in companies listed on the Jakarta Islamic Index (JII) for the period 2018-2020. The population of this study are 40 companies listed on the Jakarta Islamic Index (JII) for the period 2018-2020. The technique used in determining the sample is purposive sampling technique with a total sample of 15 companies. The results showed that working capital efficiency had an effective and significant effect on increasing profitability, while liquidity had a positive and insignificant effect on increasing profitability. The R-square value of 0.674286 indicates that the 67.42% increase in profitability indicated by ROE can be influenced by working capital efficiency and liquidity, while 32.58% is influenced by other variables outside of these variables.